Aspectos da morfologia e biologia reprodutiva de uma população de Scinax argyreornatus em Majé, no Estado do Rio de Janeiro (Amphibia, Anura, Hylidae) - Carnaval, Ana Carolina Oliveira de Queiroz (1997)
This dissertation is about the morphology, natural history, reproduction and development of a population of Scinax argyreornatus (Miranda-Ribeiro, 1926) from Campo Escoteiro Geraldo Hugo Nunes, a property of União dos Escoteiros do Brasil, in Magé, state of Rio de Janeiro, Brazil. The morphology and the osteology of adults are described and discussed, as well as some notes on the natural history of the species including reproduction sites, breeding seasons, behavior, mating calls and clutch description. The morphology of the larvae is also described, with observations on its development in captivity. Comparisons with specimens from other localities, such as Linhares and Santa Teresa, in the state of Espírito Santo; Mangaratiba, Maricá, Nova Iguaçu, Rio de Janeiro and Seropédica, in the state of Rio de Janeiro; and Ubatuba, in the state of São Paulo, are made. The results are compared to the available literature information on this species and also on other species of the genus, specially those associated to the "catharinae" and the "perpusillus" groups.